A Novel Homozygous Mutation in the FUCA1 Gene Highlighting Fucosidosis as a Cause of Dystonia: Case Report and Literature Review - Wali, Gautam; Wali, G. M.; Sue, Carolyn M.; Kumar, Kishore R. (Neuropediatrics, 2019)
Background Fucosidosis is a rare lysosomal disorder caused by mutations in the FUCA1 gene. We describe here a novel homozygous mutation in FUCA1 in an Indian fucosidosis case. Furthermore, we summarize the clinical and genetic findings in the most recently reported individuals with fucosidosis.Case The proband is an 8-year-old boy born to consanguineous parents. He had generalized dystonia and bilateral spasticity as well as coarse facies, dysostosis multiplex, recurrent infections, angiokeratoma corporis diffusum, and visceromegaly. Whole exome sequencing analysis detected a homozygous canonical splice variant in the FUCA1 gene [Chr1(GRCh37):g.24172346C > T; NM_000147.4:c.1261–1G > A], not previously reported as causative of a human phenotype. Low levels of α-fucosidase in patient leukocytes and a positive qualitative urine based thin layer chromatography test for fucosidosis confirmed the diagnosis. Our literature review identified 89 cases of fucosidosis since the last major review. We show that dystonia is a rare manifestation (12%) and that only a small minority of cases receive treatment with transplantation (3.37%).Conclusion We report a novel homozygous mutation in FUCA1 as the cause of severe neurological phenotype including generalized dystonia. Early recognition of fucosidosis may be important for consideration of promising treatment options, such as bone marrow transplantation.
Keywords: FUCA1; fucodosis; dystonia; spasticity; whole exome sequencing; case report